Climate smart agriculture: assessing needs and perceptions of California's farmers - Ikendi, Samuel; Pinzón, Natalia; Koundinya, Vikram; Taku-Forchu, Namah; Roche, Leslie M.; Ostoja, Steven M.; Parker, Lauren E.; Zaccaria, Daniele; Cooper, Mark H.; Diaz-Ramirez, Jairo N.; Brodt, Sonja; Battany, Mark; et al. (Frontiers in Sustainable Food Systems, 2024)
California is the largest agricultural economy in the United States; however, its current and projected climate risks pose significant challenges. Farmers will need to adapt to climate change in their farming practices. The goal of this needs assessment was to understand farmers' perceptions and experiences with climate change exposures; the risk management practices they currently use; and what tools and resources would assist them in making strategic decisions. A statewide survey was conducted through Qualtrics with farmers (n = 341). Results showed that 67% of the farmers agree (agree + strongly agree) that climate change is happening, and 53.1% agreed that actions are required. Moreover, historically underrepresented farmers were very concerned about climate change-related impacts related to water, temperatures, and natural disasters. Farmers are currently implementing adaptation practices related to water management, soil health, and renewable energy and are also seeking insurance and government assistance programs to increase agricultural resilience. They also expressed interest and a high need for information on those adaptation practices to acquire skills and knowledge to manage various challenges of farming in variable climates. Also, the assessment established that farmers (47.5%) use decision-support tools, mostly weather stations (22.4%); and 51.9% indicated their interest in using online tools designed to translate climate information into forms that support production decision-making. Farmers (60.8%) responded that they would or may attend workshops to learn about adaptation practices. The findings of this needs assessment will inform the development of extension education programs on climate-smart agriculture for farmers in California and elsewhere.